Fulfillment of The Needs of Aini’s Character in Andrea Hirata's Novel of Orang-Orang Biasa (Study of Abraham Maslow's Humanistic Psychology) - Nur Indah Sari; Muhammad Rapi Tang; Nensilianti Nensilianti (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract.This research focuses on analyzing the forms of efforts to meet the level of needs of Aini’s  character in Andrea Hirata's Novel Orang-Orang Biasa using the humanistic psychology study of Abraham Maslow. The variables of this research are the forms of efforts to fulfill needs which consist of five levels including physiological needs, the need for security, the need for love and affection, the need for esteem and the need for self-actualization. These levels will determine the success of a person's actualization. This research is a qualitative descriptive study and data collection is done by using library techniques. The results showed that the character Aini was able to reach the stage of self-actualization even though the other needs under her were not fulfilled optimally, namely the need for security was not fulfilled. Aini's character has been able to reach her full potential and contribute to others and her environment. This proves that in order to reach the stage of self-actualization, the characters in Andrea Hirata's Novel Orang-Orang Asli do not have to fulfill these five levels of need. The Aini character can actualize himself because of a large motivation with him.Keywords: psychological, figure, humanistic needs